Churning power losses of ordinary gears: a new approach based on the internal fluid dynamics simulations. (8th September 2014) - Concli, Franco; Gorla, Carlo; Della Torre, Augusto; Montenegro, Gianluca
Abstract The increasing need of more and more efficient gearboxes implies the need of predictive models in order to compare, during the design stage, different design solutions. The models provided by literature are mostly experimentally derived and not accurate on real applications. A new trend suggests the adoption of computational fluid dynamics (CFD) for the calculation of the no‐load losses of gear transmissions. In this sense, literature provides some works, but most of them involve only one single phase. In this paper, the real operating condition in which the gears are immersed in an oil lubricant mixture is studied. Adopting an open‐source code, OpenFOAM®, the influence of some operating and geometrical parameters on the churning losses has been investigated. The aims are both to provide data that can be effectively used by engineers in the design practice and to prove, once again, CFD to be an effective approach for this kind of investigations. Copyright © 2014 John Wiley & Sons, Ltd.